2018
DOI: 10.1093/jmcb/mjx052
|View full text |Cite
|
Sign up to set email alerts
|

Tgfbr2 inactivation facilitates cellular plasticity and development of Pten-null prostate cancer

Abstract: Mutations in tumors can create a state of increased cellular plasticity that promotes resistance to treatment. Thus, there is an urgent need to develop novel strategies for identifying key factors that regulate cellular plasticity in order to combat resistance to chemotherapy and radiation treatment. Here we report that prostate epithelial cell reprogramming could be exploited to identify key factors required for promoting prostate cancer tumorigenesis and cellular plasticity. Deletion of phosphatase and tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…To validate whether the increase in BMP signaling was involved in Pten -deficient tumors, we treated Pten -deficient prostate organoids and mouse prostate tumors with a selective inhibitor against BMP signaling, which resulted in blunted organoid passaging potential and a delay in tumor progression in vivo. These results are in line with a previous report showing that loss of TGFβ signaling has been linked to prostate cancer progression in Pten -deficient tumor, in part through upregulation of BMP signaling ( Zhao et al, 2018 ). Here, we identify the ligand BMP5 as prime driver of Pten -deficient cancer progression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To validate whether the increase in BMP signaling was involved in Pten -deficient tumors, we treated Pten -deficient prostate organoids and mouse prostate tumors with a selective inhibitor against BMP signaling, which resulted in blunted organoid passaging potential and a delay in tumor progression in vivo. These results are in line with a previous report showing that loss of TGFβ signaling has been linked to prostate cancer progression in Pten -deficient tumor, in part through upregulation of BMP signaling ( Zhao et al, 2018 ). Here, we identify the ligand BMP5 as prime driver of Pten -deficient cancer progression.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, basal stem cells are constitutively multipotent in the developing prostate, where they populate the luminal cell layer through asymmetric cell divisions ( Ousset et al, 2012 ; Shafer et al, 2017 ; Wang et al, 2014a ). In prostate cancer, basal and luminal stem cells can both act as tumor-initiating cells and are thought to contribute to tumor recurrence ( Choi et al, 2012 ; Goldstein et al, 2010 ; Wang et al, 2009 ; Wang et al, 2013 ; Zhao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gery et al showed that TMEFF1 expression in brain tumor tissue exhibited a significantly low level compared to normal brain tissues, and tumor cell lines with low TMEFF1 expression are more likely to show a strong proliferative capacity and a malignant profile 6. Similar results were also validated in colon cancer and prostate cancer,8,15 indicating that TMEFF1 plays a role as an anticarcinogenic gene in these tumors. However, the role of TMEFF1 in ovarian cancer has not yet been elucidated.…”
Section: Discussionmentioning
confidence: 87%
“…Harms and Chang found that, by binding with the co-receptor, Cripto-1, TMEFF1 interrupted the binding of Cripto-1 to the ALK4 receptor and, thus, inhibited the effects of nodal signals, further mediating the TGF-β signaling pathway to regulate the growth of cells and tissues 13,16. In a recent study, a deficiency of TGF-βR2 in prostate cancer negatively regulated TMEFF1 and thus activated the BMP signaling pathway to influence the prognosis of patients 15. Here, we discovered, for the first time, that TMEFF1 participated in the malignant biological behavior of ovarian cancer by activating the MAPK pathways and the PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Tmeff1 is also proven to be a direct target of TGF-β2/Smad2/3 signalling in hair follicle stem cell; as a result, TGF-β signalling counterbalances BMP-mediated effects by upregulating the expression of Tmeff1 [56]. Moreover, a study in prostate cancer shows that Tmeff1, which is induced by TGF-β signalling, also causes Smad1 and Smad5 to degrade through its interaction with Smurf1, thus inhibiting the BMP signalling pathway [57].…”
Section: The Potential Mechanisms Regulating the Antagonism Between Tmentioning
confidence: 99%